Foreign Investor’s Interest and Tax Avoidance: Contingency Perspectives Depended on Country’s Protection Level and Law Systems - Dielanova Wynni Yuanita; Christine Novita Dewi; Arief Zuliyanto Susilo; Kusharyanti Kusharyanti (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
This study investigates differences in firms’ tax avoidances between multinational and national. Furthermore, it investigates the differences between firms’ contingent behavior because of the country’s investor protection level and law systems. This research takes into account the firms’ tax avoidance phenomenon. Besides that, it proposes novelties as follows. First, this study highlights that multinational firms tend to avoid taxes higher than national ones. Second, it induces the dividend catering theory related to the country’s investor protection. The latest, it persuades that country’s investor protection, and law systems make firms contingent on their tax avoidance behaviors. This study finds that firms where they live in high investors’ protection countries and common law did higher tax avoidance than others. The findings imply that these firms could grow higher than others. It means that this study suggests economic consequences. The consequence is that a country should increase its investors’ protection level and somehow redefine its law systems. Therefore, it could enhance its capital market and subsequently improve the national welfares.